2020
DOI: 10.1111/maec.12609
|View full text |Cite
|
Sign up to set email alerts
|

Reef microhabitats mediate fish feeding intensity and agonistic interactions at Príncipe Island Biosphere Reserve, Tropical Eastern Atlantic

Abstract: A habitat can be defined as the environment in which a species lives, being distinguished through their physical and biological characteristics such as substrate and resource availability (Clements & Shelford, 1939; Ricklefs & Relyea, 2018). In marine ecosystems, habitat characteristics, such as benthic composition, have been proposed to determine the structure and functioning of marine communities (Ferreira, Gonçalves, & Coutinho, 2001; Gratwicke & Speight, 2005). On tropical reefs, the benthic assemblages ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…For example, on Príncipe Island, Cowburn (2018) mapped four subtidal habitats and four coastal habitats along the island. In addition, a recent study investigated the role of four different reef microhabitats in shaping biological interactions of fishes (Canterle et al 2020). Regarding São Tomé Island, the scenario is very similar to that of Príncipe.…”
Section: Marine and Freshwater Ecosystemsmentioning
confidence: 99%
“…For example, on Príncipe Island, Cowburn (2018) mapped four subtidal habitats and four coastal habitats along the island. In addition, a recent study investigated the role of four different reef microhabitats in shaping biological interactions of fishes (Canterle et al 2020). Regarding São Tomé Island, the scenario is very similar to that of Príncipe.…”
Section: Marine and Freshwater Ecosystemsmentioning
confidence: 99%
“…This showed that non-native species can disrupt this important component of ecosystem functioning, especially large mammals, which are seldom native on oceanic islands. Other quantitative studies at the community level have assessed how reef microhabitats mediate fish agonistic interactions (Canterle et al 2020), and how land use and host species influence richness, prevalence, and co-infection patterns of haemosporidian bird parasites (Reis et al 2021). A quantitative, species-specific study used stable isotopes to reveal that juvenile São Tomé Green Turtles adapt their diet preferences to the available food sources and, in contrast with expectations, are not strict herbivores (Hancock et al 2018).…”
Section: Species Interactionsmentioning
confidence: 99%
“…Although there is evidence of reef fish interacting with patch selection at the reefscape level, their roving foraging is more site-attached and constrained by diel movements from central refuges in comparison to migratory terrestrial herbivores (Nash et al 2015, Davis et al 2017b. Furthermore, reef herbivory patterns are often confined to small areas and sometimes microhabitats, even for more largebodied parrotfishes (Fox and Bellwood 2013, Brandl et al 2015, Carlson et al 2017, Davis et al 2017b, Canterle et al 2020, Puk et al 2020. For these reasons, our observation methods are proportional with previously observed spatiotemporal scales of reef fish herbivory, but, as most things in ecology, observed short-term foraging patterns here are dependent on both spatial and temporal scale.…”
Section: Generality Of Foraging Metricsmentioning
confidence: 99%